Associativismo ambiental como resposta à sustentabilidade e contribuição para a ecologia urbana - Delton Mendes Francelino (2023)
In recent centuries, humanity has intensified the processes of environmental and ecological spoliation of the Earth and its ecosystems, based, above all, on areas of financialization of human and non-human life. In view of this, and the various crises noted in urban environments, it is necessary that proposals be made so that this hostile paradigm can be transformed into models of society that can really lead to what is conventionally called sustainability. The objective of this Thesis is to discuss/propose Environmental Associativism as a contribution to Urban Ecology and, thus, to sustainability, especially from its social, humanistic, educational and ecosophical dimensions. From the gift, articulated by Mauss (2008 [1925]), Sociology for Urban Ecology and a Treaty for Environmental Existence are proposed, based on research about environmental NGOs, which moves people to join in favor of causes ecological and an immersive experience, with ethnographic elements, within the scope of the actions of one of them. In addition, a method called “Ecocultural Mapping” was elaborated, which culminated in the creation of the House of Science and Culture of Barbacena, one of the direct results of this Research. Methodologically, the Thesis was distributed in 4 Notebooks and, as a theoretical framework, it was established: correlation between Environmental Associativism and social movements from gift theorists such as Mauss (2008 [1925]), Martins (2002), Caillé (2002 ) in addition to Touraine (1965) and Castells (1999); discussions related to sustainability (or sustainability crisis) via ecopedagogy (GADOTTI, 2000); perspectives of Ecosophy (GUATARRI, 1989) and basic elements of Urban Complexity and Ecology (MORIN, 2000; 2008) (NIEMELA, 2011) (ROGERS; GUMUCHDJIAN, 2015); Theories of Justice (RAWLS, 2004), Freedom as Development (SEN, 2001) and indigenous perspectives from Kaka Werá Jecupé (2006). For immersion, the methods of Narrative Research and Life Experience (CLANDININ; CONNELY, 2011) were followed. The general structure of the Thesis was guided by the models of Bardin (2011) and Gil (1985), in a qualitative and interpretive perspective, something also contextual to the approaches of the Research Group "Societas - Tourism, Heritage, Social and Labor Relations", from UFMG, to which the author of this research is affiliated.